2019
DOI: 10.2217/cer-2018-0097
|View full text |Cite
|
Sign up to set email alerts
|

Real-world US healthcare costs of psoriasis for biologic-naive patients initiating apremilast or biologics

Abstract: Aim: Biologics and apremilast have advanced psoriasis management by adding treatment options. This study evaluated persistence, adherence and healthcare costs among biologic-naive patients receiving apremilast or biologics. Methods: Administrative claims data for adults starting apremilast or biologics from 1 January 2013 to 30 June 2016 were matched based on demographics. Results: Apremilast (n = 703) and biologics (n = 1378) had similar baseline characteristics. 12-month persistence and adherence rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
7
15
0
Order By: Relevance
“…Our findings are consistent with prior analyses among commercially insured, biologicnaive patients with psoriasis, which found similar treatment persistence rates and switch rates and significantly lower total healthcare costs at 12 months among patients initiating apremilast compared with those initiating a biologic [32,33]. To our knowledge, there are no similar studies in the literature conducted in patients with PsA who were treated with apremilast.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are consistent with prior analyses among commercially insured, biologicnaive patients with psoriasis, which found similar treatment persistence rates and switch rates and significantly lower total healthcare costs at 12 months among patients initiating apremilast compared with those initiating a biologic [32,33]. To our knowledge, there are no similar studies in the literature conducted in patients with PsA who were treated with apremilast.…”
Section: Discussionsupporting
confidence: 90%
“…Logistic regression was used to estimate the propensity score for individual patients with the following variables: age, gender, region, payer (commercial or Medicare Advantage), plan type, index year, prescriber specialty (dermatology, rheumatology, or other), Charlson comorbidity index score, pre-index healthcare costs, number of prior systemic agents (i.e., acitretin, cyclosporine, methotrexate, sulfasalazine, and leflunomide), and prior use of non-steroidal anti-inflammatory drugs, cyclooxygenase-2 inhibitors, corticosteroids, or phototherapy. These measures were identified as variables that were possibly related to both exposure cohort membership and outcome and were selected on the basis of the literature [ 32 , 35 ] and available data from the CDM database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study are consistent with a US-based study (Feldman and colleagues), which used a large administrative claims database to evaluate persistence, adherence, and healthcare costs among biologic-naive psoriasis patients treated with either apremilast or biologics. 12 The authors reported that 12-month persistence and adherence rates were similar for apremilast and biologics (44.4% vs 44.6% and 73% vs 74%, respectively) while total healthcare costs were significantly lower for apremilast versus biologic users (US$32 304 vs US$49 875; P < .001). These findings further support the use of apremilast as a cost-savings treatment for patients with moderate to severe plaque psoriasis.…”
Section: Discussionmentioning
confidence: 96%
“…In the first group with severe psoriasis, the company has claimed apremilast to be an additional line of management before starting biologicals and as a safe drug in the second group to whom the biological agents are not indicated at present. The evidence review group of this committee was highly critical of the company's claim on cost-effectiveness of the drug (e.g.,: a recently published study[ 78 ] funded by the company has shown a similar adherence and lower total healthcare costs with apremilast vs. biologic users), and concluded that the most probable incremental cost-effectiveness ratio for PASI >10 and a DLQI ≥10 group was about ≤30,300 per quality-adjusted-life-year (QALY), and this was higher than the threshold level normally regarded as cost-effective. The similar value for the second group (DLQI ≤10) would be double considering the otherwise less expenditure that would incur in this group with less severe disease.…”
Section: Cost Analysismentioning
confidence: 99%